Long-term Stability Assessment of Geological Sequestration of Carbon Dioxide Based on Mineral Carbonation - Liu, Bing (International Journal of Natural Resources and Environmental Studies, 2025)
Geological sequestration of carbon dioxide (CO2), being one of the important methods to deal with anthropogenic climate change, is to reduce the large scale emission to the atmosphere. Among all the trapping mechanisms, mineral carbonation, i.e., the reaction between CO₂ and silicate minerals to form stable, solid carbonate minerals, is considered the most secure and long-term solution to effectively isolate CO₂. This paper carries out a thorough and extended examination of the long-term stability of CO2 sequestered through in-situ mineral carbonation. It probes the key geochemical reactions shaping the change of injected supercritical CO₂ into solid mineral forms, focusing mainly on mafic and ultramafic rock formations abundant with olivine, pyroxene and plagioclase. The assessment framework described here looks at main interdependent factors that affect secure storage for an extended amount of time. Includes a detailed analysis of intrinsic reaction kinetics of silicate dissolution, evolution of host rock’s geomechanical property under coupled thermo-hydro-mechanical-chemical (THMC) stress, and the whole-scale integrity of the overlying caprock. Investigate how varying porosity and permeability brought on by competing mineral dissolution and carbonate precipitation alter the reservoir’s hydraulic properties and long term containment system. In addition to that the paper talks about the role of advanced numerical modeling of the reactive transport to predict the behavior of the storage reservoir over a span of few decades to millennial scales. And they’re important for predicting the rate of mineralization, the extent of the carbonate precipitates, and any geomechanical risks like earthquakes or cap rock fracturing. Lastly we look at state-of -the -art observation and inspection technologies that are needed for observing the subsurface plume and verifying the advancing mineral carbonation and certifying the long -term stable and environmentally safe sequestration project. The integrated assessment shows that although mineral carbonation provides the most solid solution for carbon dioxide storage, it is still based on the strict, site-specific examination of geological, geochemical, and geomechanical parameters from the laboratory scale to the field scale.